Departure difficulty score vs final difficulty score. The effect of performance in elite rhythmic gymnastics - Leandro, C.; Avila-Carvalho, L.; Sierra-Palmeiro, E.; Bobo-Arce, M. (Athens Journal of Sport, 2016)
The aim of this study was to determine how the difference between the departure difficulty score, and the final difficulty score, in the different type of elements affects the performance success in elite rhythmic gymnastics. Two hundred eighty-eight individual routines performed at the World Championship 2013 were analysed. A non-parametric test-Kruskal-Wallis test, was applied to determine whether there were significant differences between different level groups. The results show significant differences between the departure difficulty score and final difficulty score, which increase as the level of performance decreases. Rotations, DER and Mastery are the main types of difficulty elements responsible for this difference. These results suggest that the judges and coaches do not have the same perception of the evaluation criteria of the difficulty elements. The findings can contribute to improve the definition criteria of the difficulty elements and to clarify the specific needs of the training program.